2014
DOI: 10.1371/journal.pone.0094084
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Levels in Patients with Alzheimer's Disease: A Meta-Analysis

Abstract: BackgroundSerum uric acid (UA) could exert neuro-protective effects against Alzheimer's disease (AD) via its antioxidant capacities. Many studies investigated serum UA levels in AD patients, but to date, results from these observational studies are conflicting.MethodsWe conducted a meta-analysis to compare serum UA levels between AD patients and healthy controls by the random-effects model. Studies were identified by searching PubMed, ISI Web of Science, EMBASE, and the Cochrane library databases from 1966 thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
29
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 97 publications
5
29
0
2
Order By: Relevance
“…Chen et al , in a meta-analysis of case–control studies (n=2708 participants), found no significant difference between patients with AD and healthy controls in SUA level 10. Another recent meta-analysis found lower SUA level in AD but not vascular nor mixed dementia 6.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al , in a meta-analysis of case–control studies (n=2708 participants), found no significant difference between patients with AD and healthy controls in SUA level 10. Another recent meta-analysis found lower SUA level in AD but not vascular nor mixed dementia 6.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the putative adverse effect of UA on cardiovascular outcomes, UA may contribute to cognitive impairment and dementia risk via increased risk of cerebrovascular disease 13. Most studies that investigated the link between SUA level and dementia were cross-sectional, with risk of bias (review in refs 6 and 10), and longitudinal studies are scarce. Thus, more longitudinal population-based cohort studies are needed to better unravel the complex link between UA and cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated HCys in brain microvessels may be implicated in the disruption of the blood-brain barrier [51] and induction of excitotoxicity in cells expressing glutamate receptors of the N-methyl-D-aspartate class [52]. Other biomarkers considered relevant to AD are: low levels of plasma uric acid [53,54], high levels of serum 3,4-dihydroxybutanoic acid (C 4 H 8 O 4 ), docosapentaenoic acid (C22:5) [55], and hexacosanoic acid (C26:0) [56], the presence of insulin resistance and high insulin-like growth factor expression [57][58][59], impaired glycemic levels [60], mitochondrial damage and increased mitochondrial O-linked N-acetylglucosamine transferase activity [61], the presence of a dyslipidemic profile [31,[62][63][64][65][66], deregulation of plasma orexin [67][68][69][70], and high levels of the secreted heparin-binding glycoprotein YKL-40 [71,72] (Table 2). Additionally, the CSF milieu is altered in subjects presenting AD.…”
Section: The Population and Individual Levels: Epidemiological Studiementioning
confidence: 99%
“…Another systematic review assessed the association of sUA with Alzheimer’s dementia 12. Based on 11 case–control studies including 2,708 participants, the sUA levels were not significantly different between patients with Alzheimer’s dementia and healthy controls, and the standardized mean difference (SMD; same as the effect size) for sUA was −0.50 (95% CI −1.23 to 0.22), not statistically significant 12.…”
mentioning
confidence: 99%